Identifying Factors Influencing Entrepreneurial Marketing with a Sustainable Tourism Approach in the Post-COVID-19 Era - Paydarfard, Mehrab; Alizadeh Meshgani, Fataneh; Azad, Naser (Business, Marketing, and Finance Open, 2025)
The aim of this study is to identify the factors influencing entrepreneurial marketing with a sustainable tourism approach in the post-COVID-19 era. This study was conducted using thematic analysis. The research method is fundamental in terms of purpose. The statistical population consisted of theoretical (academic) and practical (managers, expert consultants, and tourism sector specialists) experts, among whom 14 individuals were purposefully selected based on their knowledge and experience. Semi-structured interviews were the primary data collection tool. Following the summarization of the interviews, coding and concept analysis were performed. The reliability of the study was assessed using inter-coder reliability, which was calculated as 82%, exceeding the baseline threshold of 60% and indicating acceptable reliability. The findings identified the factors influencing entrepreneurial marketing with a sustainable tourism approach in the post-COVID-19 era, comprising 11 dimensions and their subcomponents. These factors were categorized into 11 main themes: networking, advertising, tourism impact content, creativity, cultural tourism value, opportunity-seeking, customer orientation, innovation orientation, risk-taking, resource leveraging, and value creation, along with 68 sub-themes or components.